Nilai Humanisme dalam Q.S Al-Balad - Muklas Ridoi (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2023)
This article will lead us to the knowledge of the concept of Qur'anic humanism, especially in Al-Balad. The concept of Qur'anic humanism can be used as an antidote against increased dehumanization. As we know, humanitarian problems have always occurred, even from the creation of the Prophet Adam to this contemporary period. Humanism from the Qur'an, which in the corridor of Islamic humanism, will be used as one way to realize the humanist life among Muslims in particular and all mankind in general. This research uses the theory of discursive Islamic anthropology from Talal Asad as an approach. Talal Asad, an anthropologist, considers that Religion should be viewed and explained uniquely and under the prevailing socio-historical context, not by the analogy of words alone. Therefore, Talal Asad offers a theory of cultural anthropology that examines Islamic culture from three points of view: the culture of the past, the present (past cultural changes), and the conformity of present culture with the future. The results of this research will be able to prove that the Qur'an can be integrated with various sciences to answer problems in the past or contemporary.